Factors Influencing the Timeliness and Completeness of Appropriate Staging Investigations for Patients with Stage I–III Lung Cancer in Southeastern Ontario - Shahad AlGhamdi; Nilah Ahimsadasan; Weidong Kong; Michael Brundage; Elizabeth A. Eisenhauer; Christopher M. Parker; Andrew Robinson; Andrew Giles; Geneviève C. Digby (Current Oncology)
(1) Background: Comprehensive and timely lung cancer (LC) staging is essential for prognosis and management. The Lung Diagnostic Assessment Program (LDAP) in Southeastern (SE) Ontario aims to provide rapid, guideline-concordant care for suspected LC patients. We evaluated factors affecting the completeness and timeliness of staging for stage I–III LC patients in SE Ontario, including the impact of LDAP management. (2) Methods: This was a population-based retrospective cohort study using the LDAP database (January 2017–December 2019), linked with the Ontario Cancer Registry, to identify newly diagnosed LC patients. A Cox model approach identified variables associated with staging completeness and timeliness. (3) Results: Among 755 patients, 459 (60.8%) were managed through LDAP. Optimal staging was achieved in 596 patients (78.9%), 23 (3.0%) had alternative staging, and 136 (18.0%) had incomplete staging. In the adjusted analyses, LDAP management was associated with a higher likelihood of complete staging (OR 2.29, p < 0.0001) and faster staging completion (β = −18.53, p < 0.0001). Increased distance to PET centres was associated with a longer time to complete staging (β = 8.95 per 100 km, p = 0.0007), as was longer time to diagnosis (β = 21.63 per 30 days, p < 0.0001). (4) Conclusions: LDAP management in SE Ontario significantly improved staging completeness and shortened staging time for stage I–III LC patients.